2002
DOI: 10.1037/0735-7044.116.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol induces hypothalamic progesterone receptors but does not activate mating behavior in male hamsters (Mesocricetus auratus) before puberty.

Abstract: This study investigated pubertal changes in neural and behavioral responses to estradiol. Gonadectomized pre- and postpubertal male hamsters (Mesocricetus auratus) were treated with 0.00, 0.05, 0.10, or 0.25 mg estradiol and tested 1 week later for sexual behavior with a receptive female. Estradiol activated behavior in postpubertal, but not prepubertal, males. In contrast, estrogen receptor alpha (ERalpha) and progesterone receptor (PR) immunoreactivity in forebrain nuclei that mediate mating behavior was sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Previous studies using these time-released pellets have shown prepubertal and adult males treated with the same size pellet experience similar levels of the steroid, e.g., testosterone [15, 16, 17], estradiol [18], or corticosterone [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using these time-released pellets have shown prepubertal and adult males treated with the same size pellet experience similar levels of the steroid, e.g., testosterone [15, 16, 17], estradiol [18], or corticosterone [19]. …”
Section: Discussionmentioning
confidence: 99%
“…The sexually naive subjects received a standardized behavior test between 1700 and 2030 h EST (Meek et al, 1997;Romeo et al, , 2002Schulz et al, 2004). Following a 5 min acclimation to the test chamber, male subjects interacted with a stimulus female for 15 min.…”
Section: Sexual Behaviormentioning
confidence: 99%
“…In reviewing the literature, we found studies that examined the effects of estradiol on progesterone receptors experimentally. This literature indicates that estradiol up-regulates estrogen and progesterone receptors [13] and can induce expression of hypothalamic progesterone receptors [19]. As a result, we believe that the indirect effect of estrogen on progesterone receptors (i.e., up-regulation of progesterone receptors in the tumor and hypothalamus) changed the natural history of the meningioma and enhanced tumor growth in our patient.…”
Section: Tumor Growth In First Examinationmentioning
confidence: 72%
“…Estradiol up-regulates progesterone receptors through α-estradiol receptors and can also stimulate hypothalamic progesterone receptors in the Medial Pre optic Nucleus (MPN) [13]. Some studies show that estradiol plays an important role in the ontogenic expression of progesterone receptors during postnatal uterine maturation in rats [14].…”
Section: Meningioma: the Unusual Growth In A Transsexual Patient Aftementioning
confidence: 99%